UPAYA PENINGKATAN KEMAMPUAN PERKALIAN BERSUSUN DENGAN MENGGUNAKAN MEDIA PAPAN KARTU BERWARNA PADA PESERTA DIDIK KELAS 4 - Afrian Decky Mahendra; Dhea Ayuni Mulia; Karolina Aditya Susanti; Supriyono (LPPM Universitas Cipta Mandiri, 2025)
This classroom action research aims to improve the mathematics learning outcomes of grade 4 students in one of the elementary schools in Surakarta City on the material of stacked multiplication. Based on initial observations, it was found that students' understanding of stacked multiplication material was still low. This study used a classroom action research design consisting of two cycles. The research subjects were 21 grade 4 students in one of the elementary schools in Surakarta City in the 2024/2025 academic year. The action applied was the provision of learning media in the form of coloured card boards to help students understand the concept of stacked multiplication. Data were collected through learning outcome tests, observation of student and researcher activities, and documentation. Data analysis was carried out quantitatively descriptive to see the improvement of learning outcomes and qualitative descriptive to analyse changes in student and researcher activities. The results showed a significant increase in students' mathematics learning outcomes. In cycle I, the average test score of learning outcomes was 67.61 with a percentage of classical completeness of 48%. In cycle II, the average score increased to 81.90 with the percentage of classical completeness reaching 86%. Observations also showed an increase in student activity and participation during the learning process. It was concluded that the application of learning media in the form of coloured card boards was effective in improving the learning outcomes of mathematics in the form of stacked multiplication material for the students.